Renalase's Expression and Distribution in Renal Tissue and Cells - Wang, Feng (Public Library of Science, 2012)
To study renalase's expression and distribution in renal tissues and cells, renalase coded DNA vaccine was constructed, and anti-renalase monoclonal antibodies were produced using DNA immunization and hybridoma technique, followed by further investigation with immunological testing and western blotting to detect the expression and distribution of renalase among the renal tissue and cells. Anti-renalase monoclonal antibodies were successfully prepared by using DNA immunization technique. Further studies with anti-renalase monoclonal antibody showed that renalase expressed in glomeruli, tubule, mesangial cells, podocytes, renal tubule epithelial cells and its cells supernatant. Renalase is wildly expressed in kidney, including glomeruli, tubule, mesangial cells, podocytes and tubule epithelial cells, and may be secreted by tubule epithelial cells primarily.